2007
DOI: 10.1002/zaac.200700173
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenophanes with Interannular Nitrogen‐Aluminum Bridges – Synthesis and Structure

Abstract: The reaction of 1,1Ј-bis(trimethylsilylamino)ferrocene (1) with trimethyl-or triethylaluminum proceeds by elimination of methane or ethane, respectively, to novel ferrocenophanes 2a,b containing an N 2 Al 2 bridge. Addition of pyridine to 2 affords the pyridine adducts of 1,3-diaza-2-alkylalumina-[3]ferrocenophanes (4a,b) and of AlR 3 . The [3]ferrocenophanes 4 can be converted into 2 by addition of AlR 3 . The solution-state structure of the new compounds follows from a consistent set of NMR spectroscopic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Figure 1 (trace B) shows for 3a that the Ga–methyl groups (a) and (b) slowly exchange their positions. This had not been observed in comparable experiments for the corresponding aluminum compound, and it indicates that the coordinative Ga–N bonds are somewhat weaker than the Al–N bonds 15c.Figure 2 proves that there is also intermolecular exchange, if GaMe 3 is present. In the cases of the pyridine adducts 4 ,Figure 3 shows that the intermolecular exchange between the pyridine adducts 4a and Me 3 Ga(py) is rather slow on the NMR timescale.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 1 (trace B) shows for 3a that the Ga–methyl groups (a) and (b) slowly exchange their positions. This had not been observed in comparable experiments for the corresponding aluminum compound, and it indicates that the coordinative Ga–N bonds are somewhat weaker than the Al–N bonds 15c.Figure 2 proves that there is also intermolecular exchange, if GaMe 3 is present. In the cases of the pyridine adducts 4 ,Figure 3 shows that the intermolecular exchange between the pyridine adducts 4a and Me 3 Ga(py) is rather slow on the NMR timescale.…”
Section: Resultsmentioning
confidence: 96%
“…The reactions of 1,1′‐bis(trimethylsilylamino)ferrocene ( 1 ) with trimethyl‐ and triethylgallium are summarized in Scheme . The products 3a , b are analogous to those of aluminum 15c (Scheme ). However, more harsh reaction conditions and a large excess of GaR 3 are required to eliminate two equivalents of methane or ethane (see Me 2 Si[N(Bu t )GaMe 2 ] 2 26, and the structurally characterized bis(amido)‐bridged digallane [‐CH 2 N(Bu t )GaH 2 ] 2 27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a lithium N,N-borylsilylamide, it was shown that the nitrogen atom must be regarded as sp 2 -hybridized although its formal coordination number is four [17]. The unique nature of the NSiMe 3 amide unit is also evident by comparing the δ 29 Si value of 3 (δ 29 Si -9.6) with that of the corresponding aluminum derivatives 6 containing an N 2 (AlR 2 ) 2 unit [δ 29 Si ϩ14.9 (R ϭ Me), ϩ14.4 (R ϭ Et) [15]]. The nitrogen atoms in the bridging NSiMe 3 groups in 6 can be described as fourcoordinate ammonium-type nitrogen atoms, whereas those in 3 are of the amide-type in spite of the intramolecular association in the N 2 Li 2 unit.…”
Section: Nmr Spectroscopic Studies In Solutionmentioning
confidence: 99%
“…Although the coordination number of the nitrogen atoms can be counted as four, the structural parameters do not support the presence of ammonium-type nitrogen atoms, in agreement with the 29 Si NMR data. Most significantly in this respect are the fairly short Si-N bond lengths in 3 (both 168.5(6) pm; to be compared with data for 6 (R ϭ Et)[15]: 179.3(5), 180.0(5) pm). Thus, the Si-N bond lengths are sensitive to the nature of the nitrogen atom, and short bond lengths are typical of an sp 2 -hybridised amide-type nitrogen atom, whereas longer distances are typical of amine and ammonium-type nitrogen atoms.…”
mentioning
confidence: 96%